Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.

solving systems of equations by substitution y=9×-9 y=9

Sagot :

Okay, you substitute the y in y=9x-9. It gives us, 9=9x-9. you add nine to both sides to eliminate the -9 on the right side of the equation. So far we have, 18=9x. Divide both sides by 9. We get 2=x. And thats your answer.
y = 9x - 9
y = 9

   9 = 9x - 9
+ 9        + 9
18 = 9x
 9      9
  2 = x
y = 9x - 9
y = 9(2) - 9
y = 18 - 9
y = 9
(x, y) = (2, 9)
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.